Meningkatkan Kemampuan Bahasa Inggris Anak Melalui Media English Flash Card - Asifa Jelita Sebayang; Malida Putri (Yayasan Literasi Sains Indonesia, 2022)
English is an important thing in globalization era. In Indonesian, students learn English start form early age. Since first time go to school, student will find English in list of subject. But, it’s not make sure student can speak englisht fluently. in fact so many children in Indonesia not know how to speak English even basic vocabulary. The same things happened to one of the children at the Mercy Clement Orphanage who needed help to learn English not because he feeling have to, but learn because he love it. The process of learning was carried out in the PKL 1 mini project activities. Using the casework method throught the general intervention, start from Engagement Intake Contract, Assesment, Planning, Implementation, Evaluation, and Termination. Problem Solving in this process uses English Flash Card as a media to learn. The purpose of this program was make client have interest at English so he want to learn about English without coercion.